EQUADIFF 15 History, Personalities, Plenary and Invited Abstracts, and Program - Stránská, Jana (Masaryk University Press, 2022)
Equadiff 15 - Conference on Differential Equations and Their Applications - is an international conference in the world famous series Equadiff running since 70 years ago. This booklet contains conference materials related with the 15th Equadiff conference in the Czech and Slovak series, which was held in Brno in July 2022. It includes also a brief history of the East and West branches of Equadiff, abstracts of the plenary and invited talks, a detailed program of the conference, the list of participants, and portraits of four Czech and Slovak outstanding mathematicians.